PENYALAHGUNAAN BADAN HUKUM P.T. DAN PERLINDUNGAN HUKUM TERHADAP PEMEGANG SAHAM MINORITAS - Sunarsi, Dessy (E-Journal Widya Yustisia, 2005)
PT low corporation abuse that do by management can loss minority Stakeholders. To give protection for minority Stacieholders. Undang-undang No. 1 tahun 1995 put into doctrine effect Piercing The Corporate veil to part of PT, put into league EHQUETE and derivative right for minority Stackeholders